A new genus and new species of fan worms (Polychaeta: Sabellidae) from Atlantic and Pacific Oceans—the formal treatment of taxon names as explanatory hypotheses - de Matos Nogueira, João Miguel; Fitzhugh, Kirk; Rossi, Maíra Cappellani Silva (Zootaxa, 2010)
Members of Parasabella minuta Treadwell, 1941, subsequently moved to Perkinsiana, were collected during a survey of rocky intertidal polychaetes along the state of São Paulo, Brazil. Additional specimens, which are referred to two new species, were also found in similar habitats from the Bocas del Toro Archipelago, Caribbean Panama, and Oahu Island, Hawaii. A phylogenetic analysis of Sabellinae, including members of P. minuta and the two new species, provided justification for establishing a new generic hypothesis, Sabellomma gen. nov., for these individuals. Formal definitions are also provided for Sabellomma minuta gen. nov., comb. nov., S. collinae gen. nov., spec. nov., and S. harrisae gen. nov., spec. nov., along with descriptions of individuals to which these hypotheses apply. The generic name Aracia nom. nov., is provided to replace Kirkia Nogueira, López and Rossi, 2004, pre-occupied by a mollusk.